Comparative Analysis of Indonesia’s Minimum Capital Requirements for Foreign Direct Investment - Luh Putu Yeyen Karista Putri; Miriam Imarhiagbe; I Made Chandra Mandira; Eric Gordon Withnall; Putu Yasodhara Sthita Brahmani Duarsa (Universitas Negeri Semarang, 2023)
This research seeks to examine the compatibility of the Indonesian minimum capital requirement for foreign direct investment companies (FDI) with the national treatment obligation under international investment agreements (IIAs). The requirement is compared with investment requirements under Australian and Austrian Law. This research combines the normative legal research method with law and economics by conducting cost and benefit analysis (CBA). The national treatment protects foreign investors from less favorable treatment against domestic investors. The minimum capital requirement is contrary to national treatment because it is only applicable to FDI companies. However, not every IIA involving Indonesia provide a national treatment clause. To determine violation, the two-tier test must be conducted by analyzing the scope of the obligation and applicable exception. Some IIAs provide exceptions where a state can give different treatment to foreign investors for the sake of public interest. Indonesia justifies this requirement because it gives several benefits namely preventing foreign investors from controlling vital sectors, protecting MSMEs from unfair competition, and ensuring liquidity. Nevertheless, the benefits cannot be achieved due to weak supervision. The requirement can be easily circumvented through nominee agreements. Based on CBA, the requirement creates more harm than good. It is promiscuously applied to all business fields and is more burdensome compared to investment requirements in Australia and Austria. The solution proposed is either improving supervision or adjusting the requirement to be more consistent with the national treatment. The government can also protect national interests by empowering MSMEs and using more relevant criteria.